Assessing the nutritional composition of sweet corn (zea mays l. var. saccharata) stover and kernel corn (zea mays l. var. indentata) stover for ruminant feed - Nasir, Aina Azyan Abd; Kamaruddin, Nurul Aini (Journal of Asian Scientific Research, 2023)
Corn stover, which includes stalks, leaves, and husks left in the field after harvest, holds promise as a feed source for ruminant livestock due to its nutritional value. However, a lack of research on its nutritional composition has led to wasteful practices like open burning and disposal. Therefore, this study aims to determine and compare the nutritional value of corn stover between sweet and kernel corn. The samples of corn stover were collected at Universiti Sultan Zainal Abidin Farm. All samples were subjected to the cleaning, chopping, drying, and grinding processes before undergoing nutritional analysis using proximate analysis. The proximate analysis was measured based on the percentage of crude protein, ash, crude fibre, moisture, and fat. The results indicate that sweet corn stover exhibits the highest nutritional value (p< 0.05) in terms of ash, crude protein, and fat, with percentages of 5.44%, 19.04%, and 3.86%, respectively, particularly in its leaves. Additionally, the stalks of sweet corn stover contain the highest percentages of moisture (4.89%) and crude fiber (27.05%). This study found that sweet corn stover is more suitable for ruminant feed because it contains the highest levels of essential nutrients like crude protein, fat, and ash.